Regulation of nonspecific acid phosphatase in Salmonella: phoN and phoP genes. - Kier, L D (1979)
Mutations in Salmonella typhimurium strains lacking nonspecific acid phosphatase mapped in two unlinked loci. One of these, phoP, was cotransducible by phage P22 with purB, whereas the second, phoN, was cotransducible by phage P1 with purA. Mutants with temperature-sensitive nonspecific acid phosphatase activity (measured in whole cells) were also isolated. A phoN mutant with thermolabile whole-cell activity was isolated directly from wild-type LT-2. Several other mutants with temperature-sensitive enzyme activity were also isolated as revertants of phoN mutants. These data suggest that phoN might be a structural locus for nonspecific acid phosphatase. The observation that a mutation resulting in high level of nonspecific acid phosphatase mapped in phoP suggests a possible regulatory role for this locus.